ANALYSIS OF THE IMPACT OF EMOTIONAL INTELLIGENCE AND HEDONISM LIFESTYLE ON PERSONAL FINANCIAL MANAGEMENT OF STUDENTS IN MAKASSAR CITY - Khumairah Nurmagfirah Samsir; Abdul Rahman Laba; Fauzi R Rahim (Paulus Journal of Accounting (PJA), 2023)
This study aims to analyze the impact of emotional intelligence and hedonic lifestyle on students' personal financial management .Healthy personal finance is an important aspect of student life to achieve financial stability, reduce stress, and improve quality of life. However, various factors such as emotional intelligence and hedonic lifestyle can influence management behaviorstudent finance. Research method This research uses a correlational quantitative research type. The population is Students majoring in Accounting at the Faculty of Economics and Business Class of 2021, Hasanuddin University. The results of this study prove that emotional intelligence has an effect on personal financial management. Likewise, the hedonistic lifestyle has a significant positive effect on student personal financial management.